2004
DOI: 10.1890/03-0007
|View full text |Cite
|
Sign up to set email alerts
|

Removal Experiment Reveals Limited Effects of a Behaviorally Dominant Species on Ant Assemblages

Abstract: Ant communities are thought to consist of a competitive hierarchy of interacting species, with an assemblage of subordinate species being structured by a dominant species. Mensurative and behavioral studies suggest a significant role for competition in structuring ant communities, although there are few experimental studies to support this contention. We examined the effect of the dominant ant Iridomyrmex purpureus on the ant fauna of sandstone outcrops in southeastern Australia. We conducted a mensurative sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
99
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 50 publications
6
99
2
Order By: Relevance
“…Under natural conditions, fire ants simply do not occur in this habitat; therefore, normally have little or no effect on the natural ant community (17,28). Previous manipulative experiments have also revealed that dominant ant species may lack widespread competitive effects, instead only negatively impacting ecological equivalents (24,26,27). In this system, native species such as P. morrisi and P. dentata have similar-sized workers, similar diets, large colonies, and high abundance (28), and can thus be described as ecologically similar to S. invicta.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Under natural conditions, fire ants simply do not occur in this habitat; therefore, normally have little or no effect on the natural ant community (17,28). Previous manipulative experiments have also revealed that dominant ant species may lack widespread competitive effects, instead only negatively impacting ecological equivalents (24,26,27). In this system, native species such as P. morrisi and P. dentata have similar-sized workers, similar diets, large colonies, and high abundance (28), and can thus be described as ecologically similar to S. invicta.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the success of S. invicta and many other invasive ant species is also thought to result primarily from behavioral dominance and release from natural enemies that allows them to attain numerical superiority and competitively suppress co-occurring species (20,22,23). However, experimental demonstration of competition in ant communities is uncommon, especially for invasive species, and very few manipulative studies exist (24)(25)(26); to our knowledge, only King and Tschinkel (27) have previously manipulated entire populations of ants over multiple years.…”
mentioning
confidence: 99%
“…Ants may respond to increased favorability in a number of ways, including an increase in worker numbers (Gibb and Hochuli 2004), the formation of new nests, often through nest budding or relocation to more favorable environments (Rosengren 1986, Gibb andHochuli 2003), or increased alate production (Pontin 1969). This suggests that the two year time frame for this experiment is adequate to detect responses from ant assemblages.…”
Section: Treatmentsmentioning
confidence: 99%
“…This group is behaviourally and numerically dominant in most ecosystems in Australia (e.g. Shattuck, 1999;Hoffmann and Andersen, 2003;Gibb and Hochuli, 2004). The definition makes no reference to the type of resources used by this group and no previous study has tested whether ants from this group are the predominant tenders of hemipterans in any ecosystems.…”
Section: Study Sitesmentioning
confidence: 99%